THE DEPENDENCE OF CORONAL LOOP HEATING ON THE CHARACTERISTICS OF SLOW PHOTOSPHERIC MOTIONS - Ritchie, M. L.; Wilmot-Smith, A. L.; Hornig, G. (The Astrophysical journal, 2016)
ABSTRACT The Parker hypothesis assumes that heating of coronal loops occurs due to reconnection, induced when photospheric motions braid field lines to the point of current sheet formation. In this contribution we address the question of how the nature of photospheric motions affects the heating of braided coronal loops. We design a series of boundary drivers and quantify their properties in terms of complexity and helicity injection. We examine a series of long-duration full resistive MHD simulations in which a simulated coronal loop, consisting of initially uniform field lines, is subject to these photospheric flows. Braiding of the loop is continually driven until differences in behavior induced by the drivers can be characterized. It is shown that heating is crucially dependent on the nature of the photospheric driver-coherent motions typically lead to fewer large energy release events, while more complex motions result in more frequent but less energetic heating events.